Práticas teatrais na educação: será que dá jogo? - Camelo, Natalia Beloti Dias [UNESP] (2015)
This study investigates the use of theatrical practices as instrument of expression and manifestation of critical autonomous thinking. For this purpose, a field research in a public school in São Paulo with students attending the second year of high school was developed, in which meetings were proposed, which offered exposure to significant practices such as theater games, questioning and freedom of thought on their learning at school. Observing whether such practices dialogue with behaviors that manifest independent thoughts forms, through the rupture of standardized behaviors. The research presents a historical contextualization of the Art Education in Brazil, curriculum formation in the Brazilian educational system and concepts of Cultural Industry as well as their influence on behaviors and uniformed thoughts, especially in formation people, as in the case of adolescents in the research. Thus conjecture about the weakening of the free articulation of thinking ability of learners. And from this questioning, reflects how the theater can offer practical ways for adolescents perceive themselves as autonomous subject, and can act as agents of social transformation